The Effect of Kinship Structures on Smallholder Production of Groundnuts in Malawi - Bikketi, Edward (International Crops Research Institute for the Semi-Arid Tropics, 2017)
Presented by Edward Bikketi (ICRISAT), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.